The mass composition of cosmic rays near 1018 eV as deduced from measurements made at Volcano Ranch - Dova, María Teresa (2004)
Linsley used the Volcano Ranch array to collect data on the lateral distribution of showers produced by cosmic rays at energies above 1017 eV. Very precise measurements of the steepness of the lateral distribution function were made on 366 events. The current availability of sophisticated hadronic interaction models has prompted an interpretation of the measurements. In this analysis we use the AIRES Monte Carlo code to generate showers, together with GEANT 4 to simulate the detector response to ground particles. The results show that, with the assumption of a bi-modal proton and iron mix, iron is the dominant component of cosmic rays near 1018 eV, assuming that hadronic interactions are well- described by QGSJET at this energy range. The Volcano Ranch data set, as available to us, does not allow a straightforward assignment of energy for each event. It is thus not possible to give the energy dependence of the mass composition.